SURVEI MOTIVASI SISWA KELAS XI SMK NEGERI SE-KABUPATEN SEMARANG DALAM MENGIKUTI EKSTRAKURIKULER OLAHRAGA TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of the study to determine the motivation of a class XI student of SMK Negeri Semarang District as extracurricular sports in following school year 2012/2013. This research is deskiriptif using survey methods. The results showed that: motivation of students of class XI SMK N 1 Kaliwungu in following sports extracurricular school year 2012/2013 amounted to 75.7%, SMK N 1 Bawen by 77%, SMK N 1 Guava by 77.1%, SMK N 1 Bancak 77.9%, SMK N 1 Pringapus of 69.4% and overall SMK Negeri Semarang district as 75%. Conclusion This study is motivated class XI student of SMK N 1 Kaliwungu in following sports extracurricular school year 2012/2013 classified as high criteria, SMK N 1 Bawen relatively high in the criteria, SMK N 1 Guava relatively high in the criteria, SMK N 1 Bancak classified in high criteria, SMK N 1 Pringapus classified in the criteria being, while the overall motivation of students of class XI SMK Negeri Semarang District as extracurricular sports in following school year 2012/2013 belonging to the high criteria.